O tráfico de escravos nas relações externas de Brasil e de Portugal: 1822 a 1850 - Silva, Leonardo Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present thesis is focused on the traffic of slaves to Brazil, from the Portuguese colonies in Africa, seen here by the international relations undertaken by Portugal and Brazil from 1822 to 1850. It tries to understand how the internal political dynamics of these two nations were essential for the establishment of their foreign policies in regard of the africans slave trade. The relations undertaken between Brazil, Portugal and England form the structural axis of analysis, which concludes the fundamental importance of local political actions for the suppression of the slave traffic

A presente tese aborda o tráfico de escravos para o Brasil, a partir das colônias portuguesas na África, pela ótica das relações internacionais empreendidas por Portugal e Brasil entre os anos de 1822 a 1850. Busca compreender como as dinâmicas políticas internas destas duas nações foram determinantes para o estabelecimento de suas políticas externas em relação ao comércio de africanos. As relações empreendidas entre o Brasil e Portugal e destes com a Inglaterra formam o eixo estrutural da análise, que conclui a importância fundamental das ações políticas locais para a supressão do tráfico de escravos
Keywords: Escravos - Trafico - Brasil; Escravidão - Brasil; Brasil - História - 1822-1850; Slavery